PEMBANGUNAN KOMUNITAS DALAM KEGIATAN PERTAMBANGAN MERUBAH PARADIGMA BEBAN-BIAYA (COST-BURDEN) MENJADI MANFAAT-KEUNTUNGAN (PROFIT-ADVANTAGE) - Agung Firman Sampurna1 (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2006)
The paradigm of community development so far presumed, has posed communitydevelopment program as an additional development cost which highly depends on the charity of mining industries. Constitutionally, the mining industries are established for people’s welfare. Therefore, community development as a means to raising people’s welfare, especially for those residing around the mining plant, should become an integral part of the plant establishment goals. In order to improve its effectiveness, community development should be redefined from cost-burden paradigm to profit-advantage one. This shift of paradigm should be transcribed into a policy framework readily put into practice.